SURVEI KEJADIAN FILARIASIS PADA MASYARAKAT DESA TAWANGREJO KUNDURAN BLORA - Didik Sumanto; Sri Sinto Dewi (JURNAL LITBANG, 2006)
Background : On April 2005, DKK Blora found fourteen peoples that infected by elephanthiasis (/ilariasis) in Blora Central of Jawa. Tofollow up this discovery, DKK Blora do thefilariasis surveyfor 500 peoples andfound 163 peoples (48 o/o) wilh posilif filariasis infection.Objective : To do the repetition survey and tell the filariasis incident on society of Tawangrejo, Kunduran, Blora.Research method : The population of this resesrh is all of the people of Tawangrejo Blora" Accidental sampling tecnique applied in this research.Result: This researchfound 5 peoples (2,1 o/o) with positif filariasis infection.One of them infected by Wuchereria bancrofty andfour peoples infected by Brugia malayi.Conclusion : The saurce of infection assumpted from the people that come from external of Jawa with the elephantiasis condition. The incident rate offilariasis in Tawangrejo on November 2005 is 2,17 %. This rale is not too high with the early assumption that to richfor 48 %.Key words : survey, elephanthiasis, filariasis